Evaluation of Species-Specific PCR Primers for Detecting Pork DNA in Food Seasoning Products - Nur Atiqah, Khairul Adha; Lesley Maurice, Bilung; Aida Azrina, Azmi; Awang Ahmad Sallehin, Awang Husaini; Zaliha, Suadi (Malaysian Society of Applied Biology, 2025)
Food adulteration remains a critical issue, particularly in highly processed foods where DNA degradation reduces the effectiveness of species identification. This study evaluated the performance of three different lengths of species-specific primers (398, 288 & 149 bp) targeting the mitochondrial cytochrome B gene in pork and aimed to determine the most effective primer for detecting pork DNA in food seasoning products using species-specific Polymerase Chain Reaction (PCR). Furthermore, species-specific primers for bovine and chicken were applied as controls to confirm species identification. The DNA was extracted from raw meat, binary mixtures, and seasonings. Sensitivity was tested with low pork concentrations, and the applicability of pork-specific primers was further evaluated in seasoning products without halal certification to assess potential pork adulteration. The results show that the DNA extracted from raw meat samples exhibited high purity (OD260/280:1.82 –2.00) and concentration (114.83 to 257.16 ng/µL), whereas food seasoning products yielded extremely lower values of purity (OD260/280:0.97 – 1.81) and concentration (2.75 to 66.18 ng/µL). Despite DNA degradation in processed foods, PCR products remain detectable. The shortest 149 bp primer demonstrated the highest sensitivity among the primers, successfully detecting pork DNA at a minimum concentration of 1% (w/w) in a binary meat mixture. The results demonstrated the absence of pork DNA in all non-pork labelled samples. However, the detection of chicken DNA in fermented pork cube samples indicated potential mislabelling or crosscontamination during processing. These findings emphasise the importance of primer selection for detecting highly degraded DNA. This also underscores the applicability of species-specific PCR as a practical and robust approach for routine food authentication, providing a valuable tool to ensure halal compliance within the food industry.